Vanadium-Containing Ionic Liquids Derived from Complexes of Modified Edta as Catalysts of Epoxy-Anhydride Ring-Opening Copolymerization - Hanzl, Lukáš; Vinklárek, Jaromír; Litecká, Miroslava; Rebei, Marwa; Beneš, Hynek; Eisner, Aleš; Mikysek, Tomáš; Krejčová, Anna; Honzíček, Jan (Inorganic chemistry, 2024)
A new type of vanadium-containing ionic liquids (ILs) was synthesized by cation exchange from barium salts of oxidovanadium(IV) complexes stabilized by edta and its congeners (dcta, oedta, and heedta) serving as pentadentate ligands. All starting barium salts and several magnesium and cesium salts, serving as models for the cation exchange, were structurally characterized by single-crystal XRD analysis. The synthesized ILs consisting of organic cations (Bu4N+, Bmim+, and Bu4P+) and complex anions ([VO(edta)]2-, [VO(dcta)]2-, [VO(oedta)]-, and [VO(heedta)]-) were characterized by analytical and spectroscopic methods including EPR spectroscopy and cyclic voltammetry. Then, ILs were tested as catalysts for the ring-opening copolymerization of epoxy resin with cyclic anhydride showing significant catalytic activity, which led to production of highly cross-linked glassy thermosets. A detailed isothermal DSC kinetic study was performed for the most promising IL showing that the progress of cross-linking can be successfully fitted by the Kamal-Sourour model. Based on the DSC and NIR results, the initiation mechanism of the cross-linking in the presence of vanadium-containing IL was suggested. IL had ability to activate a rapid hydrolysis of anhydride cycle and the formed carboxyl groups initiated a polyesterification. In parallel, the role of imidazolium cation of IL for the initiation of chain-growth anionic copolymerization is also discussed.